Maintaining Family Harmony: Emotional Maturity and Social Support in Young Married Individuals - Heppi Maulana, Ardila; Dwi Cahya Izzati, Indah; Fitriani, Annisa (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Couples who get married certainly have goals, one of which is to form a harmonious family. In fact, it turns out that the phenomenon of disharmonious families is still widely found in the scope of sociaty of Indonesian. This can be seen divorce rate in Indonesia which still occurs a lot to this day, based on Indonesian statistical data, in 2023 as many as 463,654 divorce cases occurred. Of the high number of cases, most of them were contested divorces filed by women (wives). The number reached 352,402 cases, or about 76% of the total divorces at the national level. Many factors can affect family harmony, such as emotional maturity and social support. This study aims to determine the relationships of family harmony with emotional maturity and social support in young married individuals. This study involved 311 samples; the sampling technique used purposive sampling. This study uses quantitativ method with a correllational approach. Data collections used a family harmony scale, emotional maturity scale, and social support scale, which were then analyzed using linear regresion. The results show that emotional maturity and social support had a significant and positive with a significan value (p<0.05) and the effect was 70.2%. This mean that the high the emotional maturity and social support, the high the family harmony in young married individuals.Sepasang kekasih yang melakukan pernikahan tentu memiliki tujuan, salah satu tujuannya yaitu untuk membentuk keluarga yang harmonis. Faktanya, ternyata fenomena keluarga tidak harmonis saat ini masih banyak ditemui di indonesia. Hal ini bisa diketahui dari angka perceraian di Indonesia yang masih banyak terjadi hingga saat ini, berdasarkan data statistik Indonesia, pada tahun 2023 sebanyak 463.654 kasus perceraian terjadi. Dari tingginya kasus tersebut, sebagian besar merupakan gugatan yang diajukan oleh istri. Jumlahnya mencapai 352.402 kasus, atau sekitar 76% dari total perceraian di tingkat nasional. Banyak faktor yang dapat memengaruhi keluarga yang harmonis, seperti kematangan emosi dan dukungan sosial. Tujuan penelitian ini ialah guna mengetahui hubungan keharmonisan keluarga dengan kematangan emosi serta dukungan sosial pada individu yang nikah muda. Penelitian ini melibatkan 311 sampel, teknik pengambilan sampel menggunakan purposive sampling. Penelitian ini memakai metode kuantitatif dengan pendekatan korelasional. Pengumpulan data menggunakan skala keharmonisan keluarga, skala kematangan emosi, dan skala dukungan sosial, lalu dianalisa memakai regresi linear berganda. Hasil temuan ini menerangkan bahwa kematangan emosi serta dukungan sosial mempunyai hubungan yang signifikan dan positif dengan nilai (p<0.05) dan pengaruhnya sejumlah 70.2%. Artinya, makin tinggi kematangan emosi serta dukungan sosial, makin tinggi juga untuk mencapai keluarga yang harmonis terhadap seseorang yang menikah muda.